COVID-19: Poisoning by Military Solar Geoengineering Operations - Deruelle, Fabien (European Journal of Applied Sciences, 2025)
Background: Conflicts of interest, censorship, scientific misconduct, unscientific and liberticidal social methods characterized the COVID-19 period from governments, health authorities, the media and part of scientific community. However, military involvement seems to be at the root of the COVID-19 event. Objectives: The first part of this review is devoted to disputing the official narrative, while the second discusses the involvement of military technology during the COVID-19 period. Methods: Documents used come from official sources: PubMed; Google Scholar; ResearchGate; intergovernmental organizations; political documents; national newspapers; news agencies; writings or testimonies of politicians and scientists recognized in their field. Main results: 1/ The first mortality peak (March-April 2020) started in several very distant locations, at the same time, without leaving these areas. Mortality levels were correlated with air pollution levels. In France, a government drug protocol (Rivotril) killed thousands of elderly people; 2/ The methodology used to identify a virus does not respect the rigor of science nor the scientific method. Virus genome detection is based on computer models. SARS-CoV-2 was never isolated; 3/ For more than 20 years, a military technology known as solar geoengineering by stratospheric aerosol injection (SAI) sprays chemicals into the atmosphere to alter the climate, which constitutes the largest proportion of air pollution. These sprays target specific regions and cause extreme toxicity to the respiratory and nervous systems. Conclusion: Scientists cited in Part 1 show that there was no spread of a deadly viral respiratory pathogen. Consequently, the use of solar geoengineering by SAI, possibly composed of graphene-based nanomaterials, represents the most suitable explanation to link mortality peaks with precision of location, synchronicity, air pollution, weather, target population, without transmissible pathogens. The poisoning caused by this clandestine air pollution is deliberate, leading to a serious increase in respiratory illnesses and misleading the public and a large part of the medical profession about the origin of numerous pathologies.